2020
DOI: 10.3389/fonc.2020.00331
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin Resistance in Osteosarcoma: In vitro Validation of Candidate DNA Repair-Related Therapeutic Targets and Drugs for Tailored Treatments

Abstract: Treatment of high-grade osteosarcoma, the most common malignant tumor of bone, is largely based on administration of cisplatin and other DNA damaging drugs. Altered DNA repair mechanisms may thus significantly impact on either response or resistance to chemotherapy. In this study, by using a panel of human osteosarcoma cell lines, either sensitive or resistant to cisplatin, we assessed the value as candidate therapeutic targets of DNA repair-related factors belonging to the nucleotide excision repair (NER) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…The authors then screened known inhibitors of NER genes in order to find compounds that could increase cisplatin sensitization in vivo. NSC130813 and triptolide improved cisplatin efficacy in resistant and sensitive cell lines and displayed no evidence of cross-resistance with cisplatin [373]. These agents warrant further testing in a clinical setting.…”
Section: Alterations In Dna Repair Pathwaysmentioning
confidence: 91%
See 2 more Smart Citations
“…The authors then screened known inhibitors of NER genes in order to find compounds that could increase cisplatin sensitization in vivo. NSC130813 and triptolide improved cisplatin efficacy in resistant and sensitive cell lines and displayed no evidence of cross-resistance with cisplatin [373]. These agents warrant further testing in a clinical setting.…”
Section: Alterations In Dna Repair Pathwaysmentioning
confidence: 91%
“…Hence, targeting genes and proteins involved in the NER and BER pathway could provide an opportunity to circumvent resistance based on enhanced DNA repair mechanisms. A recent study by Fanelli and colleagues showed that silencing of ERCC1, ERCC2, ERCC3, ERCC4, or XPA was able to increase cisplatin sensitivity in the resistant U2-OS/CDDP300 and U2-OS/CDDP1 cells, and that silencing of ERCC1, ERCC2, or ERCC4 increased cisplatin sensitivity in the parental cell line U2-OS [373]. The authors then screened known inhibitors of NER genes in order to find compounds that could increase cisplatin sensitization in vivo.…”
Section: Alterations In Dna Repair Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…One attractive treatment strategy could include targeting NER factors. Fanelli and colleagues (2020) recently found that two compounds, NSC130813 (NERI02; F06) and triptolide, which inhibit DNA repair through binding of DNA repair proteins, enhance sensitivity to cisplatin in U2OS and Saos2 cells [ 190 ]. Understanding how these factors function in the context of mechanotransduction could aid in the success of NSC130813 (NERI02; F06) and triptolide in treating refractory OSA patients.…”
Section: Nuclear Mechanotransduction: Factors For Force Transmissimentioning
confidence: 99%
“…BMIL1 is highly expressed in osteosarcoma cells, and its overexpression promotes cell growth and chemotherapeutic resistance to cisplatin in osteosarcoma [ 23 ]. Cisplatin is a commonly used chemotherapeutic drug in patients with osteosarcoma, but it often causes drug resistance, so the effects of chemotherapy are not ideal [ 24 , 25 ]. However, the exact role played by BMIL1 in osteosarcoma treated with curcumin and cisplatin is not fully understood.…”
Section: Introductionmentioning
confidence: 99%